Do sports develop leadership? The impact of college varsity sports on leadership capacity and self-efficacy - Correia-Harker, Benjamin P.; Clark, Lindsey M.; Capin, Jacob J. (Frontiers in Sports and Active Living, 2025)
IntroductionEffective leadership in sports is associated with better team functioning, physical and psychosocial wellbeing, and reduced incidence of severe injuries. In spite of widespread anecdotal support, few studies have empirically evaluated leadership development in athletes. The purpose of this study was to investigate socially responsible leadership capacity and self-efficacy in college varsity athletes and determine the impact of competitive sports participation on leadership capacity and self-efficacy. We hypothesized that college varsity athletes would (1) exhibit greater leadership capacity and self-efficacy than nonathletes and (2) demonstrate greater growth in leadership capacity and self-efficacy than nonathletes.MethodsThe Multi-Institutional Study of Leadership survey was distributed to a representative sample of United States college students in 2018. The leadership outcomes of college varsity (intercollegiate) athletes and nonathletes were compared using the Socially Responsible Leadership Scale and Leader Self-Efficacy Scale. The Socially Responsible Leadership Scale has an omnibus score and six subscales: self-awareness, personal responsibility, integrity, collaboration, open-mindedness, and civic engagement. Student’s t-tests were used to compare scores on the Socially Responsible Leadership Scale and Leader Self-Efficacy Scale between athletes and nonathletes. Hierarchical multiple linear regression analyses were conducted for each leadership outcome, both with and without leadership high-impact practices.ResultsThe study contained 50,653 participants, including 8,447 college varsity athletes (age 20.3 ± 1.5 years, 56.2% women) and 42,206 nonathletes (age 20.2 ± 1.5 years, 65.9% women). While athletes reported statistically higher levels of self-awareness and leader self-efficacy but lower integrity and open-mindedness compared with their nonathlete peers, all comparisons had trivial effect sizes (all Cohen's d < 0.02; range: −0.067 to 0.159). There were no differences between athletes and nonathletes in terms of personal responsibility, collaboration, civic engagement, and the omnibus score of the Socially Responsible Leadership Scale. In regression models with and without leadership high-impact practices, athlete status explained only 0.1% or less of variance in each leadership outcome.DiscussionThe findings from this large sample of college athletes and nonathletes (n = 50,653) challenge widely held notions regarding sports and leadership, suggesting that competitive sports alone may not help people develop leadership capacity or self-efficacy. While sports provide opportunities for people to engage in leadership high-impact practices, athletes may benefit from additional resources to develop leadership skills inside and outside of sports.